Menelaah Adopsi Konsumen Pada Cashless Payment Pasca Pandemi Sebagai Upaya Menuju Cashless Society - Afrizal, Yogi Hady; Dienan Yahya, Syarief; Zakiyabarsi , Furqan (Universitas Islam Negeri Alauddin Makassar, 2023)
This research aims to understand the consumer adoption patterns of cashless payments post the Covid-19 pandemic. The research method employed in this study is qualitative with a descriptive approach. The research is focused on two study locations: Makassar City and Parepare City. The results of the study indicate that the adoption pattern of users for cashless payments post-pandemic is characterized by users preferring cashless payments due to their convenience, efficiency, financial transparency, and the rewards they receive. Currently, cashless payment facilities are still primarily concentrated in urban areas, which has an impact on the sustainability of a cashless society. Regarding the costs incurred, they are perceived to be proportional to the convenience offered, and cashless payment has become an optional choice for users in their current transactions.